Lipoxin Inhibits Fungal Uptake by Macrophages and Reduces the Severity of Acute Pulmonary Infection Caused by Paracoccidioides brasiliensis - Laura R. R. Ribeiro; Flávio V. Loures; Eliseu F. de Araújo; Cláudia Feriotti; Tânia A. Costa; Carlos Henrique Serezani; Sonia Jancar; Vera L. G. Calich (Mediators of Inflammation)
Cysteinyl leukotrienes (CysLTs) and lipoxins (LXs) are lipid mediators that control inflammation, with the former inducing and the latter inhibiting this process. Because the role played by these mediators in paracoccidioidomycosis was not investigated, we aimed to characterize the role of CysLT in the pulmonary infection developed by resistant (A/J) and susceptible (B10.A) mice. 48 h after infection, elevated levels of pulmonary LTC4 and LXA4 were produced by both mouse strains, but higher levels were found in the lungs of susceptible mice. Blocking the CysLTs receptor by MTL reduced fungal loads in B10.A, but not in A/J mice. In susceptible mice, MLT treatment led to reduced influx of PMN leukocytes, increased recruitment of monocytes, predominant synthesis of anti-inflammatory cytokines, and augmented expression of 5- and 15-lipoxygenase mRNA, suggesting a prevalent LXA4 activity. In agreement, MTL-treated macrophages showed reduced fungal burdens associated with decreased ingestion of fungal cells. Furthermore, the addition of exogenous LX reduced, and the specific blockade of the LX receptor increased the fungal loads of B10.A macrophages. This study showed for the first time that inhibition of CysLTs signaling results in less severe pulmonary paracoccidioidomycosis that occurs in parallel with elevated LX activity and reduced infection of macrophages.